The type I ribosome-inactivating protein α-MMC induced significant apoptosis of lung cancer A549 and 95-D cells by activating the caspase cascade through TNF signaling pathway - Yang, Di; Peng, Di; Li, Houke; Jia, Di; Zhou, Yiping; Hu, Bintao; Chen, Wei; Meng, Yao (Frontiers in Pharmacology, 2025)
Background:Ribosome-inactivating proteins (RIPs) are a class of toxic proteins with RNA N-glycosidase activity, primarily found in plants. Due to their antiviral, antibacterial and anti-tumor biological activities, RIPs have received extensive attention all over the world. Alpha-momorcharin (α-MMC) is a typical type I ribosomal inactivation protein, showing excellent anti-tumor activity. Lung cancer is a leading cause of global morbidity and mortality; however, current treatments remain limited, and patient prognosis is poor.Methods:In this study, α-MMC was extracted from momordica charantia seeds, and a series of in vitro studies were carried out on lung cancer A549 and 95-D cells, such as cell proliferation, cycle, apoptosis, migration to invasion, etc. Further, Western blot was used to explore the Cyclin-CDK-CKI signaling pathway, Caspase cascade and TNF signaling pathway respectively.Results:Studies have shown that α-MMC can significantly inhibit the proliferation of lung cancer A549 and 95-D cells. α- MMC can co-mediate the TNF signaling pathway to participate in cell regulation through NF-κB (down-regulated p65/p50) and MAPK (downregulated p38/JNK) signaling pathways, and activate downstream effector factors of Caspase to induce apoptosis. The expression of Cyclin D, CDK4, Cyclin A and CDK2 was downregulated by cyclin-CDK-CKI signaling pathway, thus blocking the cell cycle in G0/G1 phase or S phase.Conclusion:α-MMC exhibited significant antitumor activity against lung cancer A549 and 95-D cells, which laid the experimental foundation for clinical research and development of novel anti-tumor drugs.